Federal Tax Legislation as an Implicit Contracting Cost Benchmark: The Definition of Excessive Executive Compensation - Harris, David G.; Livingstone, Jane R. (The Accounting Review, 2002)
We examine how tax legislation that restricted firms' deductions of CEO compensation above $1 million reduced the implicit contracting cost of compensation for firms that were expected to pay below that amount and that were not directly affected by the law change. We find that firms that expected to pay their CEOs less than $1 million actually increased their CEOs' cash compensation, contrary to Congress's expectations. Moreover, the magnitude of the unexpected increase in compensation is proportional to how far the CEO's expected compensation fell below Congress's new $1 million reasonable-compensation standard. Thus, our study provides evidence that some of the largest U.S. corporations responded in a manner contrary to policymakers' expectations. Our findings also support the theory of implicit contracting costs, by demonstrating that many firms reacted in an economically rational fashion when a change in the tax law decreased their implicit costs of CEO compensation.